Advances in the diagnosis of pneumonia in children. (26th July 2017) - Zar, Heather J; Andronikou, Savvas; Nicol, Mark P
Abstract : Pneumonia remains a major cause of childhood mortality and morbidity globally. Accurate diagnosis and attribution of the causes of pneumonia are important for measuring the burden of disease, implementing appropriate preventive or treatment strategies, and developing more effective interventions. This review summarizes recent diagnostic advances in radiological techniques, specimen collection, and laboratory methods. Although chest ultrasound and chest magnetic resonance imaging are promising modalities for radiological diagnosis, their role in clinical management and their impact on outcomes need further study. Rapid, highly sensitive, multiplex laboratory tests performed on upper respiratory tract samples or induced sputum can detect nucleic acid from potential pathogens in most children with pneumonia. However, it may be difficult to attribute causality because it is often impossible to distinguish between organisms colonizing or infecting the upper respiratory tract and those causing pneumonia. Currently available host biomarkers lack accuracy for distinguishing bacterial or mixed bacterial-viral infections from viral infections. New biomarkers derived from host transcriptional profile analysis may be more accurate but require validation. Prospective studies with appropriate control populations, including studies of clinical impact, are needed to improve our understanding of the role of tests. Although progress has been made in radiological techniques and laboratory testing, current methods for diagnosing and attributing the causes of pneumonia are suboptimal.